The work hardening and softening behavior of spherical Tip/Mg-5Zn-0.3Ca composite - Cui-ju Wang; Jin-Kai Zhang; Kai-bo Nie; Chao Xu; Kun-kun Deng (Journal of Magnesium and Alloys, 2025)
To obtain the Tip with different aspect ratios, the Tip/Mg-5Zn-0.3Ca composite prepared by semi-solid stir casting was subjected to extrusion at 220℃, 180℃, and 140℃, respectively. Then, the effect of the Tip’s aspect ratio on the microstructure, mechanical properties, work hardening and softening behaviors of Tip/Mg-5Zn-0.3Ca composites was investigated. The results indicated that the Tip could be elongated obviously after low-temperature extrusion, and the aspect ratio of which would reach to 13.7:1 as the extrusion temperature deceased to 140℃. Then the “Ti/Mg” layer-like structure was formed in the Tip/Mg-5Zn-0.3Ca composite. Accompanied with the elongation of Tip, the dynamic recrystallized grains and dynamic precipitates were both refined significantly, however, the dynamic recrystallization rate changed a little. The elongated Tip endowed the Tip/Mg-5Zn-0.3Ca composites with better matching of strength and toughness without the sacrifice of elongation and bending strain. Both the work hardening rate and softening rate of Tip/Mg-5Zn-0.3Ca composites increased with the increasing aspect ratio of Tip. The formation of “Ti/Mg” layer-like structure contributed to the redistribution of strain from large aggregations to a network-like distribution, which effectively suppresses the initiation and propagation of micro-cracks, thus enhancing the plasticity of the Tip/Mg-5Zn-0.3Ca composites.